Changes in Brazilian Drosophilidae (Diptera) assemblages across an urbanisation gradient - Gottschalk,Marco S. (2007)
The present study aims to characterise the assemblages of Drosophilidae sampled from four sites subject to different levels of urbanisation, in the city of Florianópolis, South Brazil. Five samples were collected between August 2000 and August 2001 and five between August 2002 and August 2003 in each site. A gradual change in the dominant species was observed in the urbanisation gradient, with an increase in relative abundance of exotic species in urban areas. Among the native species, the relative abundance of Drosophila capricorni Dobzhansky & Pavan had an expressive decrease. In the other hand the richness in the low urbanisation site increased, probably due to the presence of urban gardens. The diversity index did not vary significantly among sites, but its correlation with evenness and richness changed.